A computerized, self‐administered test of verbal episodic memory in elderly patients with mild cognitive impairment and healthy participants: A randomized, crossover, validation study. Issue 1 (27th September 2018) - Morrison, Randall L.; Pei, Huiling; Novak, Gerald; Kaufer, Daniel I.; Welsh‐Bohmer, Kathleen A.; Ruhmel, Stephen; Narayan, Vaibhav A.
Abstract: Introduction: Performance of "Revere", a novel iPad‐administered word‐list recall (WLR) test, in quantifying deficits in verbal episodic memory, was evaluated versus examiner‐administered Rey Auditory Verbal Learning Test (RAVLT) in patients with mild cognitive impairment and cognitively normal participants. Methods: Elderly patients with clinically diagnosed mild cognitive impairment (Montreal Cognitive Assessment score 24–27) and cognitively normal (Montreal Cognitive Assessment score ≥28) were administered RAVLT or Revere in a randomized crossover design. Results: A total of 153/161 participants (Revere/RAVLT n = 75; RAVLT/Revere n = 78) were randomized; 148 (97%) completed study; 121 patients (mean [standard deviation] age: 70.4 [7.84] years) were included for analysis. Word‐list recall scores (8 trials) were comparable between Revere and RAVLT (Pearson's correlation coefficients: 0.12–0.70; least square mean difference [Revere‐RAVLT]: −0.84 [90% CI, −1.15; −0.54]). Model factor estimates indicated trial ( P < .001), period ( P < .001) and evaluation sequence ( P = .038) as significant factors. Learning over trials index and serial position effects were comparable. Discussion: Participants' verbal recall performance on Revere and RAVLT were equivalent.